The second All-Union summer school of homotetical topology - Journal, Lithuanian Mathematical (Lithuanian Mathematical Journal, 1966)
Original title in Russian and Lithuanian: Вторая Всесоюзная летняя школа по гомотопической топологии Antroji Visasąjunginė homotetinės topologijos vasaros mokykla